2001
DOI: 10.2223/jped.343
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of SNAP and SNAP-PE for neonatal mortality

Abstract: Resumo Objetivos: avaliar os escores SNAP e SNAP-PE como preditores de mortalidade neonatal na nossa UTI neonatal, comparando seus resultados. Métodos: todos os recém-nascidos admitidos na UTI neonatal no período de março de 1997 a dezembro de 1998 foram avaliados prospectivamente quanto ao SNAP e SNAP-PE com 24 horas de vida. Foram critérios de exclusão o óbito ou alta da UTI nas primeiras 24 horas de vida, as malformações congênitas incompatíveis com a vida, e recém-nascidos transferidos de outros hospitais.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…Detection of bacterial DNA in blood samples of neonates is suggested to represent a rapid and sensitive supplement to blood culture in diagnosing bacterial sepsis in neonates [ 5 , 14 , 16 ]. However, at present there are no standardised clinically evaluated methods available for detection of bacterial DNA in blood samples from neonates.…”
Section: Introductionmentioning
confidence: 99%
“…Detection of bacterial DNA in blood samples of neonates is suggested to represent a rapid and sensitive supplement to blood culture in diagnosing bacterial sepsis in neonates [ 5 , 14 , 16 ]. However, at present there are no standardised clinically evaluated methods available for detection of bacterial DNA in blood samples from neonates.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous studies, cut-offs of 33, 24 and 32 were determined on ROC analysis. [13][14][15] In the present study, evaluation of all centers using a single cut-off resulted in statistically significant differences in specificity and sensitivity. The overall mortality rate was 11.3%, but mortality rate variability between the NICU may be explained by differences in patients and resources.…”
Section: Discussionmentioning
confidence: 48%
“…Cut‐offs vary with institution. In the previous studies, cut‐offs of 33, 24 and 32 were determined on ROC analysis . In the present study, evaluation of all centers using a single cut‐off resulted in statistically significant differences in specificity and sensitivity.…”
Section: Discussionmentioning
confidence: 59%
“…The increased survival of very low birth weight (VLBW) infants due to recent advances in neonatal care has produced a new population of infants at very high risk of developing comorbidity 4 . Previous articles have evaluated the usefulness of the neonatal illness severity scores like CRIB, SNAP, SNAPPE and cumulative SNAP, to predict mortality and morbidities including ROP and BPD 15,16 . In our study, high SNAPPE-II values showed better discrimination as predictors of neonatal morbidities and as a common independent risk factor for ROP and BPD.…”
Section: Discussionmentioning
confidence: 99%